Regulation of RSPO3-LGR4 Signaling: Emerging Role in Inflammation Revealed by Network Analysis - Stojanovic, Marija; Agrawal, Devendra K (Archives of Clinical and Biomedical Research, 2025)
RSPO3, as a member of the R-spondin gene family, is a secreted molecule that enhances one of the fundamental biological pathways, the canonical Wnt signaling pathway. Once secreted from endothelial cells or macrophages, it typically binds to specific receptors from the LGR family. Additionally, LGR-independent activation of the Wnt cascade, driven by RSPOs, has also been described, mediated by heparan sulfate proteoglycans (HSPGs). LGR4 (GPR48) belongs to the G-proteincoupled receptor superfamily, subfamily B. It is widely recognized as an RSPO3-binding receptor and, thereafter, a Wnt signaling potentiator. Expression patterns of both RSPO3 and LGR4 have been found across various tissues. RSPO3 regulates stem cell maintenance in the intestine, in addition to its function in liver endothelial cells in terms of liver zonation or osteoblast differentiation. LGR4 has shown expression in hypothalamic neurons, regulating reproductive hormone secretion and control of food intake. Various studies reported the contribution of both RSPO3 and LGR4 to inflammatory cascades. Specifically, the RSPO3-LGR4 ligandreceptor interaction was shown to activate the NLRP3 inflammasome and β-catenin-NF-kB signaling cascade. Endothelial-derived RSPO3 exerts regenerative potential via the RSPO3-LGR4-ILK-AKT pathway, as presented in vitro model of inflammatory vascular injury. As a reaction to H.pylori infection, NF-κB was produced in response to RSPO3-LGR4 interaction. In order to get better insight into the signaling cascade between RSPO3 as a ligand and LGR4 as a receptor, in the context of inflammation, in silico analysis was performed. Gene input list included core Wnt pathway proteins, their downstream molecules, and various inflammatory mediators and cytokines related to RSPO3 and LGR4, as described in the literature. Network analysis included protein-protein, transcription factor-gene, and microRNAs-gene interactions. Molecules revealed from the network analysis are potential therapeutic targets in the treatment of inflammatory conditions. Further investigations are needed to test the predicted molecular pathways in vitro or in vivo. From the translational point of view, providing a proper anti-inflammatory agent in the clinical setting will be the ultimate research goal.